2010
DOI: 10.1177/1363461510379933
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Service Utilization of Somali Adolescents: Religion, Community, and School as Gateways to Healing

Abstract: This mixed-method study examines the utility of the Gateway Provider Model (GPM) in understanding service utilization and pathways to help for Somali refugee adolescents. Somali adolescents living in the Northeastern United States, and their caregivers, were interviewed. Results revealed low rates of use of mental health services. However other sources of help, such as religious and school personnel, were accessed more frequently. The GPM provides a helpful model for understanding refugee youth access to servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
122
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(127 citation statements)
references
References 38 publications
5
122
0
Order By: Relevance
“…Despite the many documented barriers in the Somali community to accessing mental health services 3,4,11 , this study found there was a great level of enthusiasm for engaging in this evidence-based intervention once it was provided in a format that met the needs of the community. In the words of the one of the CHWs upon being trained: "It is like we have [a] locked door, and you have brought us the key.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Despite the many documented barriers in the Somali community to accessing mental health services 3,4,11 , this study found there was a great level of enthusiasm for engaging in this evidence-based intervention once it was provided in a format that met the needs of the community. In the words of the one of the CHWs upon being trained: "It is like we have [a] locked door, and you have brought us the key.…”
Section: Discussionmentioning
confidence: 75%
“…Despite the availability of effective treatments for depression, these communities face disparities in access to treatment 10 . Somali refugees experience barriers in accessing services that include distrust of authorities, stigma around mental health services, and linguistic or cultural barriers 11 . There are high levels of stigma around addressing mental health in the Somali community 3 and therefore a lack of culturally options to address such concerns 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One article examined mental health service use among Somali immigrant adolescents and found that only 8% of the sample reported that they sought help from formal service providers for mental health issues (49). Another study found that 11% of Caribbean immigrants with a psychiatric diagnosis used any mental health services (versus 47% of U.S.-born Caribbeans) (34).…”
Section: Resultsmentioning
confidence: 99%
“…Refugee and immigrant children access services less than nonimmigrant children (Huang, Yu, & Ledsky, 2006;Munroe-Blum, Boyle, Offord, & Kates, 1989). An estimated 92% of immigrants and refugees deemed in need of mental health services never receive them (Birman et al, 2005;Ellis et al, 2010;Kataoka et al, 2002). Poor access to services is likely the result of multiple barriers.…”
mentioning
confidence: 98%